Magnetohydrodynamic Boundary Layer Flow Due to a Continuously Moving Flat Plate - Chiam, T.C. (Computers & mathematics with applications (1987), 1993)
The boundary layer equations arising from the effects of a continuously moving flat plate under the action of a transverse applied magnetic field are converted into a system of ordinary differential equations subject to two-point boundary conditions by using the Local Nonsimilarity Method. An iterative method incorporating the shooting method is presented for solving both the two-equation and three-equation models.